Ethics in publications: National researchers’ experiences of social sciences field in Mexico - SALAZAR-FIERRO, PETRA (2018)
Ethics guides individuals to perform good or bad actions that allow solve their problems and a bad or good ethical behavior adopted has an effect for the rest of their lives and in scientific research field ethics plays a very important role. In this work we show 24 researchers’ experiences of social sciences field and belonging to The National System of Researchers (NSR) in Mexico, about ethics in publications, specifically unacceptable and questionable ethical behavior, ethical behavior in papers evaluation by editors and conflict of interests. Data were gathered throughout a semi-structured interview and the information analysis was to read and analyze each respondents’ answer to identify the developed behavior. Researchers mentioned have known 34 experiences, 27 about ethical lacks in papers evaluation by editors or arbiters and 17 related with conflict of interests and they recognize to know ethical principles and they think it must survive in all scientific work, so they are agree apply it in their scientific and academic production, however some of them coincided in their responses regard unacceptable or questionable plagiarism behavior, which has been present in some cases and they have known situations of favoritism in proofreading to some authors or institutions, or soften project results of institutions to justify profits without obtaining efficient results and it constitutes a conflict between researchers.